The Effect Of Audit Quality, Human Resource Management, Competitive Advantage, On Financial Decisions And Financial Performance On Expedition Services - Peres Liku Datu; H. Ardi Paminto; Jamaluddin Jamaluddin (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The importance of financial management is to ensure a regular and adequate supply of funds. Optimum utilization of the company's organizational finances is of course through financial management. Financial management is an important part of the management financial governance process which includes resource mobilization, program priorities, the budgeting process, all of these activities reflect economic activity and are certainly in accordance with an economic perspective and information systems. For the continuity of good financial governance, it is hoped that appropriate analysis and evidence will be used in making financial decisions or management decisions with economic variables from the economic system through financial performance, competitive advantage, human resource management and audit quality. In a company there are elements that need to be understood such as actions, behaviors that describe everything related to financial management in making decisions in companies with logical considerations. In this study is an overview of the shipping service companies listed on the Indonesian stock exchange with financial governance and boundaries so that problems that arise in financial governance can be observed and narrowed down for a management decision. When patterns are carried out in financial governance through studies of audit quality, human resources, competitive advantage of financial performance, it is hoped that there will be influences that are closely related to each other to support each other in order to achieve a more advanced corporate financial decision, as well as an overview for making a decision that is good and right